The Role of KEAP1-NRF2 System in Atopic Dermatitis and Psoriasis - Tatsuya Ogawa; Yosuke Ishitsuka (MDPI AG, 2022)
The Kelch-like erythroid cell-derived protein with cap'n'collar homology-associated protein 1 (KEAP1)-nuclear factor erythroid-2-related factor 2 (NRF2) system, a thiol-based sensor-effector apparatus, exerts antioxidative and anti-inflammatory effects and maintains skin homeostasis. Thus, NRF2 activation appears to be a promising treatment option for various skin diseases. However, NRF2-mediated defense responses may deteriorate skin inflammation in a context-dependent manner. Atopic dermatitis (AD) and psoriasis are two common chronic inflammatory skin diseases caused by a defective skin barrier, dysregulated immune responses, genetic predispositions, and environmental factors. This review focuses on the role of the KEAP1-NRF2 system in the pathophysiology of AD and psoriasis and the therapeutic approaches that utilize this system.